Systolic anterior motion of the mitral valve associated with acute type A aortic dissection: a case report describing one-step surgery of ascending aortic replacement and interventricular septal myectomy - Naoki Yamamoto; Koji Onoda (Surgical Case Reports, 2021)
Abstract Background Systolic anterior motion of the mitral valve associated with acute type A aortic dissection is rare in daily clinical practice. The prevention of systolic anterior motion is important, because once it occurs, the hemodynamics may become unstable, leading to a critical situation. In the surgical procedure to treat systolic anterior motion, the prevention of new iatrogenic aortic intimal tears is important in the context of acute type A aortic dissection. Case presentation We present a case of systolic anterior motion in a 68-year-old woman with an acute type A aortic dissection and suspected acute relative adrenal insufficiency. Preoperative transthoracic echocardiography revealed left ventricular outflow tract obstruction due to systolic anterior motion without left ventricular hypertrophy and interventricular septal bulging due to a narrow aorto-mitral angle. We successfully performed a one-step surgery for ascending aortic replacement and interventricular septal myectomy using the needle stick technique for the treatment of systolic anterior motion. Conclusions Concomitant interventricular septal myectomy using the needle stick technique with thoracic aortic replacement is a safe and feasible technique. Interventricular septal myectomy may be effective in preventing postoperative unstable hemodynamics due to systolic anterior motion in the management of acute aortic dissection.